Patients’ right to access medical records in Malaysia / Rafidah Bolhassan - Bolhassan, Rafidah (2019)
Today’s patients nowadays are well educated, enthusiastic and actively participating in their healthcare. The right of the patient to information through access to the medical records is relevant for the patients to interact and get information about their health. Difficulty in access to medical records has been a problem in Malaysia, particularly in medical litigation case. This study explores the needs of the right of patient to access medical records and the legal positions in Malaysia, the UK and Singapore. Overall, there is a positive impact of patients access to medical records to both patients and doctors. Access to medical records improves doctor-patient communication, builds the trust, educates and empower the patients. The right of patient to access to medical record has been well-recognised as a legal right in the UK and Singapore. However, patients in Malaysia have difficulty to access their medical records and therefore have to apply for the Court's order in order to access to their medical records particularly in medical litigation. This research posits that in order to grant patient’s right to access medical record in Malaysia, there is an urgent need for the government to formulate a procedure and guideline for patient’s access to medical records, as well as to fully implement electronic medical record (EMR) in all hospitals.